Cytotoxic activity of acnistins upon human cancer cells - Chataing, Bernardo; Usubillaga, Alfredo; Pérez, César; Méndez, Ramón (Ciencia, 1970)
The cytotoxic activity against human A375 melanoma, MCF7 breast cancer and K652 leukemia cells of acnistins A, E and L, isolated from the leaves of Acnistus arborescens (L) Schletcht (Solanaceae) and the derivatives, 2,3-5,6-diepoxi-acnistin A and acnistin F, obtained in the laboratory by hemisynthesis, were examined using a microculture tetrazolium (MTT) assay. The objectives were to determine if these compounds have cytotoxic activity against cancer cells; to determine the type of interaction between acnistin A with ketoconazole and a-solamargine as well as the type of interaction between acnistin E with a-solamargine and a-chaconine, two compounds which interfere with neutral lipid metabolism. On the other hand this study was addressed to obtain evidence about acnistin moieties that are important for activity. Results indicated that acnistins A, E and L were cytotoxic to human A375 melanoma cells with IC50 values ranging between 0.19 to 80.5 ÂµM, depending on the time of exposition to the steroidal lactone. Also, acnistins A and E were cytotoxic toward MCF7 breast cancer and K652 leukemia cells, with IC50 values ranging from 10.2 to 134.4 ÂµM. The effectiveness of acnistins A and E against the human A375 melanoma cells was greater than against the other cell lines. The results suggested that presence of an a,b-unsaturated ketone, an epoxy moiety between C-5 and C-6, and an hydroxyl group at C-17 are required for activity.